A case of dengue hemorrhagic fever with myocarditis and complete heart block - Mohd Sazlly Lim, Sazlyna; Hoo, Fan Kee; Wan Sulaiman, Wan Aliaa (Pakistan Medical Association Rawalpindi Islamabad Branch, 2014)
We report a case of serologically confirmed dengue hemorrhagic fever in a 20 year-old Vietnamese male, complicated by myocarditis and asymptomatic, complete AV block.